2011
DOI: 10.1007/s11159-011-9246-4
|View full text |Cite
|
Sign up to set email alerts
|

Mother tongue instruction in Lubuagan: A case study from the Philippines

Abstract: In the modern era, the prevailing model of public education has been that of ''one size fits all'', with private schooling being a small but notable exception. Language (of instruction) was generally viewed as a minor variable readily overcome by standard classroom instruction. As researchers have sharpened their focus on the reasons for educational failure, language has begun to emerge as a significant variable in producing gains in educational efficiency. This paper reports the intermediate result of a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 6 publications
2
23
1
Order By: Relevance
“…Given the evidence in the reviewed literature, we hypothesize that children taught in their L1 language acquire a deeper understanding of academic materials leading to better academic outcomes and as such increases the measured level of A . While our research is unable to identify the exact mechanism that would cause Quechua-medium education to result in higher test scores for Quechua speaking children, other authors have suggested that stronger identification with the teacher ( Benson, 2010;Benson, 20 0 0;Enge & Chesterfield, 1996;Hovens, 2002;Lavoie, 2008;Trudell, 2005;Truong, 2012;Walter & Dekker, 2011 ) or better word recognition ( Slavin and Cheung, 2005) may be mechanisms that lead to higher test scores. We therefore expect a positive relationship between Indigenous language instruction and cognitive ability.…”
Section: Theoretical Frameworkcontrasting
confidence: 60%
See 2 more Smart Citations
“…Given the evidence in the reviewed literature, we hypothesize that children taught in their L1 language acquire a deeper understanding of academic materials leading to better academic outcomes and as such increases the measured level of A . While our research is unable to identify the exact mechanism that would cause Quechua-medium education to result in higher test scores for Quechua speaking children, other authors have suggested that stronger identification with the teacher ( Benson, 2010;Benson, 20 0 0;Enge & Chesterfield, 1996;Hovens, 2002;Lavoie, 2008;Trudell, 2005;Truong, 2012;Walter & Dekker, 2011 ) or better word recognition ( Slavin and Cheung, 2005) may be mechanisms that lead to higher test scores. We therefore expect a positive relationship between Indigenous language instruction and cognitive ability.…”
Section: Theoretical Frameworkcontrasting
confidence: 60%
“…Researchers find that Indigenous children in L1-medium classrooms engage more with their teachers ( Benson, 2010 ) and have higher academic achievement compared to children not taught in their L1 ( Benson, 20 0 0;Enge & Chesterfield, 1996;Hovens, 2002;Lavoie, 2008, Cummins, 20 0 0;Trudell, 20 05;Truong, 2012;Walter & Dekker, 2011 ). It has also been documented that children taught in their L1 have more active classroom participation ( Benson, 20 0 0 ), experience higher levels or parental engagement in schools ( Cummins, 20 0 0;D'Emilio, 1995 ), and build a stronger foundation for future literacy and acquisition of other languages ( Cummins, 20 0 0; Thomas & Collier 1997 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of various researches as regards the benefits derived from using mother tongue instruction convinced the policy makers to adopt it in the educational system of the country. The benefits underscored in these researches include enhanced scholastic capability (Cummins, 2000;Thomas & Collier, 1997;Walter & Dekker, 2011); active involvement in the class (Benson, 2000;Dutcher, 1995); accessibility to instruction (Benson, 2004;Smits, Huisman & Kruijif, 2008); and improved creative and critical thinking abilities (Brock-Utne, 2006). Studies also strengthened the relevance of multilingual education on the promotion and preservation of cultural heritage (Cummins, 2000;Wright & Taylor, 1995); increased the active involvement of parents (Cummins, 2000;Dutcher, 1995;D'Emilio, 1995); and enhanced academic performance of female learners Hovens, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this Causapin indicated that use of a second language in the mathematics classroom negatively affected confidence and performance [19]. Indeed, a recent study found that it was more beneficial to use the first language in learning mathematics [20]. Moreover, analyzing the percentage of the responses on each positive item of students' beliefs about mathematics learning and students' beliefs about mathematics problem solving as indicated in Table 3.…”
Section: The Nature Of Students' Beliefs About Mathematics Learning Amentioning
confidence: 85%